Reliability routing protocol based on vehicle density in VANET - Rong CAI; Guoan ZHANG; Li JIN (Dianxin kexue)
A reliability routing protocol based on vehicle density in vehicular Ad Hoc network was proposed to reduce the complexity of finding an optimal or sub-optimal node of the forwarding node in forwarding range,reducing the average number of hops and enhancing the reliability of the link.Firstly,the size of the unite block was set by the forwarding node according to the vehicle density in the road.And the forwarding range was cut into several equal blocks.Then the farthest block away from the forwarding node was selected.In the selected block,the neighbor node which had the longest link time was chosen as a relay node to forward according to the principle of reliability finally.Compared with EG-RAODV,the simulated results of the proposed routing protocol show that the average number of hops is less and the average distance of one-hop progress is lager,which means the proposed routing protocol can transmit the data packet to destination node more quickly.